2020
DOI: 10.29309/tpmj/2020.27.07.4011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of postoperative complications after impacted mandibular third molar extraction with conventional suturing versus tube drainage.

Abstract: Objectives: To determine the effectiveness of tube drain compared with conventional suturing on postoperative complications after extraction of impacted mandibular third molars. Study Design: Cross Sectional study (Comparative). Setting: Department of Oral & Maxillofacial Surgery, Institute of Dentistry, LUMHS Jamshoro/Hyderabad. Period: Six months duration from 12-11-2015 to 13-05-2016. Material & Methods: All the patient age from 18 to 45 years irrespective of gender, having mesioangular impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…However, because clinicians tend to stress such complications when aring informed consent or the sheets with PO instructions, patients seem to focus more attention on function(ie, chewing, swallowing, "Therefore, studies evaluating the effect of third molar surgery or perioperative medications on patients' Quality of Life (QOL) and correlating the effect with objectively measured sequelae are becoming more important to offer patients the optimal management". In this trial male participants were more than fifty percent which is in accordance with the study of Channar KA [9] in 2014, and Rajper [5] in 2020 "Stratified analyses by gender were not carried out due to the unavailability of enough individual patient data. None of the individual trials, however, suggested that there might be a genderdependent effect of CS".…”
Section: Man Femalesupporting
confidence: 63%
See 1 more Smart Citation
“…However, because clinicians tend to stress such complications when aring informed consent or the sheets with PO instructions, patients seem to focus more attention on function(ie, chewing, swallowing, "Therefore, studies evaluating the effect of third molar surgery or perioperative medications on patients' Quality of Life (QOL) and correlating the effect with objectively measured sequelae are becoming more important to offer patients the optimal management". In this trial male participants were more than fifty percent which is in accordance with the study of Channar KA [9] in 2014, and Rajper [5] in 2020 "Stratified analyses by gender were not carried out due to the unavailability of enough individual patient data. None of the individual trials, however, suggested that there might be a genderdependent effect of CS".…”
Section: Man Femalesupporting
confidence: 63%
“…Swelling of the local region is the most frequent usual complication and it usually occur after surgical procedure postoperatively (PO) because of tissue injuries [3][4] to minimize reducing PO discomfort is of important concern, both for patients and doctor. Well skilled surgeon, a time limited operation and by the application of cold dressings have a beneficial better effect on PO edema [5].…”
Section: Introductionmentioning
confidence: 99%